Differences in height, weight, and BMI in patients with mood disorders, schizophrenia, and other mental disorders vs. normal controls - Fountoulakis, Konstantinos N.; Petalidou, Nikoleta; Fountoulakis, Nikolaos K.; Nimatoudis, Ioannis; Theodorakis, Pavlos N. (Frontiers in Psychiatry, 2026)
IntroductionThe literature suggests differences in the body between the general population and patients with mental disorders. The current study aimed to search for differences between healthy controls and patients with mental disorders in terms of body height, weight, BMI, and Body surface area (BSA).Material and methodsThe study sample included 788 healthy control subjects, 76 patients with unipolar depression, 36 with Bipolar disorder, 16 patients with schizoaffective disorder, 122 patients with schizophrenia, and 78 patients with other mental disorders (a mixture of severe forms of OCD, psychotic and mood disorders other than the aforementioned, as well as severe personality disorders). The diagnosis was made according to DSM-IV-TR criteria, based on a semi-structured interview using the Schedules for Clinical Assessment in Neuropsychiatry version 2.0 (SCAN v 2.0). The height and weight of all subjects were measured. The Body mass index (BMI) and the Body surface area (BSA-D according to the Dubois method) were calculated. All variables were normalized using the rank and percentile method based on the percentiles obtained from the healthy control group. The statistical analysis included a MANCOVA with the Scheffé post hoc test.ResultsThe results suggested that depressed patients are shorter than expected, while higher BMI was observed in depressed females only. No other differences among groups were identified.DiscussionThe current study implies the presence of a developmental component in unipolar depression since this mental disorder is associated with a body measure (height) whose development is completed by late adolescence. An explanation could involve the presence of a biased negativistic assessment of the environment, which affects the functioning of the central melanocortin system, which controls appetite, food intake, and energy expenditure, and it is directly related to body development.